Iodine Nanoparticles (Niodx™) for Radiotherapy Enhancement of Glioblastoma and Other Cancers: An NCI Nanotechnology Characterization Laboratory Study - James F. Hainfeld; Sharif M. Ridwan; Yaroslav Stanishevskiy; Henry M. Smilowitz (MDPI AG, 2022)
Effective and durable treatment of glioblastoma is an urgent unmet medical need. In this article, we summarize a novel approach of a physical method that enhances the effectiveness of radiotherapy. High atomic number nanoparticles that target brain tumors are intravenously administered. Upon irradiation, the nanoparticles absorb X-rays creating free radicals, increasing the tumor dose several fold. Radiotherapy of mice with orthotopic human gliomas and human triple negative breast cancers growing in the brain showed significant life extensions when the nanoparticles were included. An extensive study of the properties of the iodine-containing nanoparticle (Niodx) by the Nanotechnology Characterization Laboratory, including sterility, physicochemical characterization, in vitro cytotoxicity, in vivo immunological characterization, and in vivo toxicology, is presented. In summary, the iodine nanoparticle Niodx appears safe and effective for translational studies toward human use.